ETDCC: Energy-Eﬃcient Transmission Scheme for Dynamic Climatic Conditions in WSN - Sunil Kumar; Prateek Raj Gautam; Tarique Rashid; Akshay Verma; Arvind Kumar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this paper, an energy-efficient transmission scheme for dynamic climatic conditions (ETDCC) has been proposed in wireless sensor networks (WSNs). This scheme is based on IEEE802.15.4 standard. In this method, open-loop and closed-loop feedback systems are used for snowfall variation. An open-loop system is utilized for snowfall-aware link quality compensation and estimation. However, closed-loop system aids to split the network into two logical regions, resulting the overhead of total control packets is minimized. According to link quality changes due to snowfall variation, the transmitting power is decided on the basis of current number of neighbor nodes and threshold power loss for each region. The simulated results depict that the proposed scheme with reduced control packets overhead adjusts transmitting power level (Plevel) to compensate link quality. This scheme based on threshold level is compared with the conventional approach that comprises the division of regions without threshold level.